Social Acceptance and Gender Differences in the Use of Dysphemism among the Urban Undergraduates in Bangladesh - Afrin, Mashfia; Kamal, Md Asif (International Journal of Education, Language, and Religion, 2025)
Dysphemism refers to the deliberate use of offensive language in communication. Prior research highlighted the factors around dysphemism especially among young people in diverse cultural settings. However, there is a limited exploration of dysphemism usage in Bangladesh, particularly among university students. This study addresses this gap by analyzing the types and frequency of dysphemism usage among urban university students in Bangladesh, along with its social and gendered dimensions. A stratified sampling approach was utilized and the data was collected via a Likert-scale survey from 100 male and female students from both public and private universities. The result indicates that dysphemistic epithets are the most common type of dysphemism among the population and significant gender differences in the usage of dysphemistic language as male students were using and getting exposed to this more than their female counterparts. Recommendations for future research are to use a more statistically robust sample size and to explore of factors influencing the usage of dysphemism and its impact on communication.